2021
DOI: 10.47176/mjiri.35.68
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implementing a mobile game on improving dietary information in diabetic patients

Abstract: ↑What is "already known" in this topic: • Educational games are growing rapidly as a tool for treating patients.• New theoretical models are emerging in the field of educational games for diabetic patients. →What this article adds: Amoo educational game, which is accompanied by intelligence, has been effective in educating calories and glycemic of food to type 2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 37 publications
(34 reference statements)
2
24
0
Order By: Relevance
“…Overall, there was a diverse population of patients diagnosed with prediabetes (glucose: 5.55-6.94 mmol/L or 100-125 mg/dL; HbA 1c : 39-46 mmol/mol or 5.7%-6.4%), type 1 DM, T2DM, and gestational DM (2-hour oral glucose tolerance test level of ≥9 mmol/L). The features of each app included food tracking [ 53 - 62 ], education, knowledge, or recommendations [ 54 - 56 , 59 - 65 ], physical activity tracking [ 54 - 56 , 59 - 62 ], weight monitoring [ 56 , 59 - 62 ], glucose monitoring [ 55 , 57 , 60 , 61 , 64 ], blood pressure monitoring [ 60 ], community support [ 54 , 59 , 60 ], feedback [ 54 - 56 , 59 , 61 , 62 , 64 ], health coaches [ 55 ], clinician portals [ 60 - 62 ], connectivity to digital health devices [ 56 , 57 ], scheduled reminders [ 56 , 58 , 59 , 62 ], gamification [ 59 , 63 ], and goal setting [ 59 ]. In addition, several targeted behavioral domains and outcomes were measured as a result of the mHealth app nutrition intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there was a diverse population of patients diagnosed with prediabetes (glucose: 5.55-6.94 mmol/L or 100-125 mg/dL; HbA 1c : 39-46 mmol/mol or 5.7%-6.4%), type 1 DM, T2DM, and gestational DM (2-hour oral glucose tolerance test level of ≥9 mmol/L). The features of each app included food tracking [ 53 - 62 ], education, knowledge, or recommendations [ 54 - 56 , 59 - 65 ], physical activity tracking [ 54 - 56 , 59 - 62 ], weight monitoring [ 56 , 59 - 62 ], glucose monitoring [ 55 , 57 , 60 , 61 , 64 ], blood pressure monitoring [ 60 ], community support [ 54 , 59 , 60 ], feedback [ 54 - 56 , 59 , 61 , 62 , 64 ], health coaches [ 55 ], clinician portals [ 60 - 62 ], connectivity to digital health devices [ 56 , 57 ], scheduled reminders [ 56 , 58 , 59 , 62 ], gamification [ 59 , 63 ], and goal setting [ 59 ]. In addition, several targeted behavioral domains and outcomes were measured as a result of the mHealth app nutrition intervention.…”
Section: Resultsmentioning
confidence: 99%
“…23,24,30 A total of 35.5% to 100.0% participants took oral antihyperglycemic medication, 19,15,22,25,26,28,29,31 11.8% to 37.8% participants injected insulin, 22,25,29,31 and 23.5% to 30% had mixed oral medication and insulin. 25,26 A total of six studies reported the duration of diabetes, ranging from 2.6 to 13.7 y 15,19,23,27,29,31 Among 15 reviewed studies, a total of eight studies were two-arm RCT intervention, 15,20,22,23,25 -28 two studies were two-arm quasi-experimental studies, 18,24 and five studies were single-group intervention. 17,19,29 -31 A total of 12 studies lasted less than or equal to three months, 15,17 -20,23 -26,29 -31 and three lasted 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 A total of six studies reported the duration of diabetes, ranging from 2.6 to 13.7 y 15,19,23,27,29,31 Among 15 reviewed studies, a total of eight studies were two-arm RCT intervention, 15,20,22,23,[25][26][27][28] two studies were two-arm quasi-experimental studies, 18,24 and five studies were single-group intervention. 17,19,[29][30][31] A total of 12 studies lasted less than or equal to three months, 15,[17][18][19][20][23][24][25][26][29][30][31] and three lasted 12 months. 22,27,28…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations